IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA PT POS INDONESIA MPC SURABAYA - Sukmawati, Ade Ayu; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the implementation of Good Corporate Governance and to find out the five principles constraints that are encountered by the company i.e.: openness, accountability, responsibility, independence, and fairness. It has been found from the result of the research that the company has implemented the Good Corporate Governance by preparing the RKAP for every fiscal year, determine task clarity and responsibility of each department within the company, establish partnerships and community development program, make regulations which prohibit all company organs in conducting transactions which contradict to the interest and taking personal benefit from the corporate activities under its management, implementing human capital management system which is based on the principles of openness, fairness, motivating and free of bias.Keywords: Openness, Accountability, Responsibility, Independence, Fairness